Teachers' and Students' Perceptions towards the Use of Arabic in Secondary Level English Language Classrooms - Hamze, Roussol Kassem (2010)
A Master of Arts Thesis in Teaching English to Speakers of Other Languages (TESOL) by Roussol Kassem Hamze Entitled, "Teachers' and Students' Perceptions towards the Use of Arabic in Secondary Level English Language Classrooms," May 2010. Available are both Hard and Soft Copies of the Thesis.